(3QSGdI GdCNdGbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3GdeSYhO Hf eMeO eOGQcdi s)
(3ChdgG (B:s
(3QSGdI ai GdGNdGb heYQaI GdaVGFd hcjajI CbSGegG dJRehG HgG heYQaI GdQPGFd s
(3BNQgG (B:s
(3hjJUhQ dYfGjI hjJNbb Cf GdeHOC GdChd Ci hLhO jNUg BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs